Phenotypic Variation in Disease Severity Among Hospitalized Pediatric Patients With COVID-19: Assessing the Impact of COVID-19 in the EPICO Study - María Camila Sossa-Alarcón; Mónica Paola Gutiérrez; Natalia Becerra; Luz Yessenia Ortegon; María Camila David; Melisa Naranjo Vanegas; Melisa Naranjo Vanegas; Gabriela Friedrich; Pablo Vásquez-Hoyos; Pablo Vásquez-Hoyos; María Lucía Mesa-Rubio; Luis Miguel Navarro-Ramirez; et al. (International Journal of Public Health)
ObjectiveTo characterize the clinical phenotypes of SARS-CoV-2 infection in hospitalized children as part of the EPICO multicenter cohort study.MethodsWe included hospitalized children with confirmed SARS-CoV-2 infection from Colombian and Spanish institutions to assess disease evolution and outcomes. Cluster analysis was performed to identify clinical phenotypes.ResultsA total of 2318 patients were included (55% male, 36% infants). Five phenotype clusters emerged: Cluster 1 (26.5%): infants without comorbidities, low PICU admissions and mortality; Cluster 2 (18.5%): respiratory comorbidities, high microorganism co-detection and mortality; Cluster 3 (11.5%): fever, gastrointestinal symptoms, high PICU admissions; Cluster 4 (32%): mild unspecific symptoms, low mortality; Cluster 5 (11.3%): adolescents without comorbidities, low co-detection and hospitalization rates. Findings were consistent across both countries.ConclusionIdentifying clinical phenotypes of SARS-CoV-2 in children may improve risk stratification and guide future management strategies.